Physicochemical characteristics of Hadhramaut Moringa peregrina seeds oil - Al-Maqtari, Maher Ail; Al-Maydama, Hussen Manaa; Bahadi, Murad Awadh; Barfed, Hani Mahfoodh (Eclética Química, 2025)
The Hadhramaut Moringa peregrina seeds oil (HMPSO) composition was characterized by Fourier transform infrared, hydrogen and carbon nuclear magnetic resonance (1H-NMR and 13C-NMR) spectroscopy. The oil was extracted from the Hadhramaut Moringa peregrina seeds using the Soxhlet method with hexane as the solvent, which reached 34.0±0.2%. The physicochemical properties showed the free fatty acid consisted of 3.18±0.5%, an acid value of 7.0±0.5 mg NaOH/g, an iodine value of 69.4±0.2 g I2/100g, saponification value of 185.1±0.1 mg KOH/g, refractive index of 1.47±0.01 at 25 °C, the moisture consisted of 0.48±0.03%, density of 0.92±0.03 g mL–1 at 25 °C, and a viscosity of 48±0.1 cP at 25 °C. The gas chromatography showed oleic acid (78.2±0.1%), palmitic acid (9.80±0.05%), stearic acid (3.6±0.1%), behenic acid (2.52±0.07%) and arachidic acid (1.83±0.05%). The major triacylglycerols of HMPSO, estimated by using high-performance liquid chromatography, were OOO (39.43%), POO (24.54%), SOO (8.18%), and AOO (6.74%). These findings provide important insights into the physicochemical properties of HMPSO; they could have significant implications for its utilization in various industries.